Innovation Strategy Through Financial Literacy Case Study on Handicraft Craftsmen in Lembang District, West Bandung Regency - Patimah, Siti; Maulana, Muhammad Fikri (STMIK Dharma Wacana, 2022)
Technological progress is something that cannot be avoided in today's life, because technological progress will run in accordance with scientific advances. Every innovation is created to provide positive benefits, provide many conveniences, and as a new way of doing activities for human life. This is also related to digital financial literacy as a technology that needs to be an understanding that needs to be mastered. The purpose of the study was to determine the implementation of innovation through digital financial literacy for Handicraft Craftsmen in Lembang District, West Bandung Regency. The research method used is qualitative with a case study approach. The data collection method used was literature study, in-depth interviews, and field observations (triangulation). As well as data analysis techniques used by using. data analysis, namely reduction, data display, and conclusion drawing/verification. Targeted outputs in conducting research for mandatory national journals sinta 3 and other outsiders are in the form of book chapters. Based on the results of the research that has been done, it is found that the handicraft craftsmen in the Lembang sub-district are related to financial literacy as a whole do not understand the finances that are carried out correctly and well. The innovation strategy that needs to be done is to be proactive with concentration where it is necessary to increase the understanding of craftsmen. In addition, the government's role is to help conduct training, technical guidance and assistance which is carried out continuously and consistently. Suggestions that can be conveyed by researchers are that in conditions where there is still limited understanding of finance, the coaching activities carried out need to be carried out continuously and consistently. In addition, craftsmen are expected to have the desire to be able to improve their financial understanding